Determinants of Indonesia's Export Performance: The Role of the Generalized System of Preferences (GSP), Gross Domestic Product, and Export Competitiveness - Fitria Ramadani; Denny Saputera (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The decline in the effectiveness of the Generalized System of Preferences (GSP) tariff preference scheme and the dynamics of export product competitiveness raise questions about the factors that influence Indonesia's export performance. This study aims to analyze the influence of GSP tariff preferences, Gross Domestic Product (GDP), and export competitiveness as measured by the Revealed Comparative Advantage (RCA) index on Indonesia's Crude Palm Oil (CPO, HS 1511.10) export performance to India during the 2010–2024 period. The study uses a quantitative associative-causal approach with the Moderated Regression Analysis (MRA) method based on secondary data obtained from UNCTAD, the World Bank, and the ITC Trade Map. The results show that GSP tariff preferences have no significant effect on export performance, while GDP and RCA have a positive and significant effect. Simultaneously, the three variables are able to explain 72.1% of the variation in export performance. In addition, RCA does not moderate the relationship between GSP and export performance, but significantly strengthens the influence of GDP on export performance. These findings indicate that Indonesia's improved export performance is more determined by strengthening economic capacity and product competitiveness than by solely utilizing preferential trade facilities. The research's implications emphasize the importance of enhancing industrial competitiveness and refining export policy strategies.